TEKNOLOGI DAN KARIER - Meike Kurniawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Technology is becoming more and more advanced and growing rapidly. One form of technological progress is the internet. The use of internet media (including social media) is increasing rapidly, especially during the Covid-19 pandemic. The rapid advancement of internet technology has brought a number of positive or negative impacts for users.As the largest internet users, teenagers are most vulnerable to being affected by internet use, so they need to get supervision and direction, to prevent them from negative impact of using the internet. Seeing this phenomenon, teenagers (high school students & college students) need to be equipped with knowledge about how to take advantage of technological developments in a positive way for career planning. By holding